TOOLS OF MANAGEMENT ACCOUNTING IN IMPROVING THE MARKETING PROCESSES OF INDUSTRIAL COMPANIES IN CUBA - VALDES PEREZ, DAYANA; Parreño García, Jorge Oswaldo; Valdés Pérez, Asiris Odalys (IJRDO - Journal of Business Management, 2019)
Over the years, the products and services are increasingly complex and with it the demands of customers in terms of quality, time and price. For the aforementioned, in order to be successful, is necessary to have an adequate management and relationship of the areas in the entity, relying on tools such as those that make up Management Accounting, which serve as support both for planning and for control therefore for decision making. Planning is not aimed at eliminating risks, assuming them is essential for progress, ensuring that they are detected. In this sense apply a procedure based on the Cost – Volume – Utility model, for making managerial decisions, aimed at improving the commercialization process in cuban industrial companies, constitutes the objective for this investigation, that is validated through a case study applied to an intentional sample dedicated to the production of fruit juices in Cuba; for this purpose, several methods were used at the theoretical level such as structured interviews, surveys, expert criteria and a method was formulated for the analysis of the different variables that make up the research, as well as the evaluation of two scenarios that allowed to diagnose the situation of the industry, recognizing that the proposed procedure allows decisions to be made to improve commercialization in the juice line of industrial.